Prospek Pengembangan Usaha Keripik Pisang di Bandarlampung - Marlinda Apriyani; Hartrisari Hardjomidjojo; Darwin Kadarisman (Institut Pertanian Bogor, 2014)
This study conducted to formulate a possible scenario in the future (prospective strategic). The scenario is based on conditions that may occur in the future toward on the key factors that influence the development of banana chips industry in Bandarlampung. This study aimed to: (1) identify the factors that influence the development of banana chips Small Medium Enterprises (SMEs) industry in Bandarlampung, and (2) determine the formulation of banana chips SME development strategy in Bandarlampung, and (3) determine the operational recommendations for the development of banana chips SMEs in Bandarlampung. The analysis tool is the Prospective Analysis to predict the possibilities that occur in the future and prepare a strategic action needs to be done and see if changes are needed in the future. The studied showed that the critical success factors of banana chips business development in order to increase market share and become a superior product in Bandarlampung are (1) technical capability, (2) managerial skills, (3) access to information, (4) the production process, and (5) availability of raw materials. Formulation of enterprise development strategies carried out by combining the results of stakeholder analysis and a prospective analysis, to generate an optimistic scenario for the development of banana chips in Bandarlampung. Operational recommendations for the development of banana chips in Bandarlampung prepared using a prospective analysis: (1) increase the technical ability of entrepreneur, (2) increase the managerial skills, (3) increased access to information, (4) modern processes for production, and (5) increasing the availability of raw materials.